HIDROLISIS SELULOSA ECENG GONDOK (Eichhornia crassipe) MENJADI GLUKOSA DENGAN KATALIS ARANG AKTIF TERSULFONASI - Putri Anggraeni; Zaqiyah Addarojah; Didi Dwi Anggoro (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2013)
This research engage water hyacinth (Eichhornia crassipes) as source of cellulose for hydrolysis into glucose using sulfonated activated carbon as catalyst. The aimsof this research are to know optimum conditions for hydrolysis water hyacinth into glucose which includes hydrolysis temperature, hydrolysis times, and the weight of catalyst. This research design uses three steps, first is making catalyst,then hydrolysis of cellulose and the last is testing content glucose of filtrate. The data results was plotted on a mathematical model and then optimized using the software Statistica 6.0 by Response Surface Methodology method (RSM). The result obtained by use of a mathematical model for relationship activator combination temperature, time and weight of catalyst for content glucose : Y = 11,601+2,353 x1 – 1,041x1² + 2,463 x2 – 1,554 x2² -2,847x3 – 1,316 x3² + 0,025 x1x2 - 0,885 x1x3 + 0,228 x2x3. The optimum conditions of hydrolysis variable for content glucose obtained from the graph fitted response surface and contour plot that indicates optimum hydrolysis temperature in the range 130°C to 170°C, the optimum hydrolysis time in the range 130 minutes to 210 minutes, and weight of catalyst in the range 3 gr to 20 gr. From this study are expected any further research on application glucose from hydrolysis of water hyacinth as raw material for bioethanol production.